Effect of the serum 25-hydroxyvitamin D level on risk for short-term residual dizziness after successful repositioning in benign paroxysmal positional vertigo stratified by sex and onset age - Wu, Jing; Jiang, Chun-Yan; Bai, Ying-Xia; Xu, Qian; Sun, Xu-Hong; Pan, Hui; Shu, Liang; Liu, Jian-Ren; Chen, Wei (Frontiers in Neurology, 2023)
Objective: Low serum 25-hydroxyvitamin D (25(OH)D) level is relevant to both of the occurrence and recurrence of benign paroxysmal positional vertigo (BPPV), which is the most common form of peripheral vestibular disorder. However, whether it also contributes to residual dizziness (RD) after successful repositioning maneuvers is unknown. Therefore, this study aimed to explore the correlation between serum 25(OH)D level and short-term RD severity in patients with BPPV after successful repositioning maneuvers. Methods: Totally 251 BPPV patients after successful repositioning were enrolled and prospectively followed up for one week (W1). Serum 25(OH)D values were detected by chemiluminescence immunoassay at enrollment (W0). In addition, we explored the relationship between 25(OH)D values at baseline and RD severity at W1 in different subgroups stratified by gender and onset age (early-onset, ≤ 50 years; late-onset, > 50 years). Results: The serum 25(OH)D level of female patients was significantly lower than that of male patients (15.9±6.8 vs 19.8±6.6 ng/ml, p<0.001). Its level also decreased in early-onset patients compared to late-onset ones (15.3±5.9 vs 18.0±7.3 ng/ml, p=0.003). In addition, early-onset females had lower 25(OH)D values compared with that of late-onset females (14.0±5.5 vs 17.1±7.2 ng/ml, p=0.004). However, this difference was not present between early- and late-onset males. Among early-onset female patients, the 25(OH)D values of moderate-to-severe RD group were lower than those of minor or no RD group (10.9±3.3 vs 14.7±5.7 vs 15.0±5.9 ng/ml, p=0.046). Multivariate analysis found that decreased 25(OH)D values were related to the occurrence of moderate-to-severe RD in early-onset female patients (OR=0.801; p=0.022). This effect did not exist in late-onset female or male BPPV patients. Conclusions: Age and gender differences of serum 25(OH)D levels exist in BPPV patients. Decreased 25(OH)D level in early-onset female BPPV patients may increase the odds of moderate-to-severe RD one week after successful repositioning maneuvers.